Benson's Effect of Relaxation With Murotal Surah Ar-Rahman Against Emergencies in Hypertensive Patients At The Jati Health Center - Tri Widiyati; Sukarmin Sukarmin; Diana Tri Lestari (CV. Inara, 2026)
Hypertension is a chronic disease that is often accompanied by psychological problems in the form of anxiety. Uncontrolled anxiety can worsen the condition of hypertensive patients. One of the nonpharmacological efforts that can be made to lower anxiety levels is Benson Relaxation combined with the Qur'anic murottal. This study aims to determine the effect of Benson Relaxation with murottal on anxiety levels in hypertensive patients. This study uses a quasi experiment design with a pretest and posttest with control group approach. The research sample amounted to 42 respondents who were divided into intervention groups and control groups, each as many as 21 respondents, with purposive sampling techniques. Anxiety levels are measured using the Hamilton Anxiety Rating Scale (HARS). The research instrument showed that the item correlation value ranged from 0.529–0.727 and Cronbach's Alpha value was 0.756. The data were analyzed using the Wilcoxon test. The results showed that in the intervention group there was a decrease in anxiety levels, with the median value before the intervention being 17.00 and after the intervention being 12.00, and the value p = 0.000 (p < 0.05), which means that there is a significant difference. Meanwhile, in the control group, there was no significant difference in anxiety levels, with the median value before treatment being 20.00 and 20.00 after treatment, and the p value = 0.058 (p > 0.05). Benson relaxation with murottal is effective in lowering anxiety levels in hypertensive patients and can be recommended as a non-pharmacological supportive therapy in nursing services. L,l,